2015
DOI: 10.1186/s13104-015-1594-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with VIA positive result among clients screened at Family Guidance Association of Ethiopia, south west area office, Jimma model clinic, Jimma, Ethiopia 2013: a cross-sectional study

Abstract: BackgroundCervical cancer is the 2nd most frequent and top killer cancer among women in Ethiopia. Prevalence and factors associated with visual inspection with acetic acid (VIA) positive result is not studied yet at the study area.MethodsA cross-sectional study was conducted at Jimma model clinic of Family Guidance Association of Ethiopia, from September 11, 2013 to October 11, 2013. Pertinent data of 334 screened clients were transferred to Epidata version3.1 using checklist, double data entry verification do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
57
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(82 citation statements)
references
References 17 publications
16
57
8
1
Order By: Relevance
“…Similar finding was observed in a study conducted in Jimma, Ethiopia that showed clients who started intercourse less than 16 years were 2.2 times more likely to have a precancerous cervical lesion (AOR [95% CI] 2.2 [1.1, 4.3]) [13]. This association was also seen in a case–control study of cervical cancer risk factors in Indian women where the maximum risk of cervical cancer was increased in women with a sexual debut at < 12 years old (OR = 3.5) and also increased in women who had extramarital sexual relationships (OR = 5.5) [14].…”
Section: Discussionsupporting
confidence: 85%
“…Similar finding was observed in a study conducted in Jimma, Ethiopia that showed clients who started intercourse less than 16 years were 2.2 times more likely to have a precancerous cervical lesion (AOR [95% CI] 2.2 [1.1, 4.3]) [13]. This association was also seen in a case–control study of cervical cancer risk factors in Indian women where the maximum risk of cervical cancer was increased in women with a sexual debut at < 12 years old (OR = 3.5) and also increased in women who had extramarital sexual relationships (OR = 5.5) [14].…”
Section: Discussionsupporting
confidence: 85%
“…The overall VIA positivity rate among the women in our study was 4.3%. VIA positivity rates reported by other cross-sectional studies in developing countries range from 4% to 16% [9,16,22,24], which makes the prevalence found in our study among the lowest observed in African women. The variability across studies may be due to other factors than disease prevalence.…”
Section: Discussioncontrasting
confidence: 61%
“…We found no association between VIA positivity and age. Results from previous studies on the association between age and VIA positivity are inconsistent; some have found a higher risk of VIA positivity with increasing age [19,21], while others report the opposite or no association [22,23]. Finally, in line with some others, lifetime number of partners [22] and education [8] were not significantly associated with VIA positivity in our study, whereas other studies found that increasing number of lifetime partners [23] and a low educational level [21,23] increased the likelihood of a positive VIA test.…”
Section: Discussionmentioning
confidence: 88%
“…An interviewer-administered semi-structured questionnaire was adapted by reviewing similar studies [ 17 , 19 , 22 ]. The questionnaire includes questions about the socio-demographic and economic characteristics, reproductive, lifestyle and sexual behavior of the study participants (See S1 File ).…”
Section: Methodsmentioning
confidence: 99%